Implementation of saving matrix to determine distribution route of Kalog Express Surakarta. (April 2019) - Rosanti, A A; Yuniaristanto,; Sutopo, W; Hisjam, M
Abstract: Transportation is important in the courier services industry. Determination of vehicle routes must be carried out appropriately and optimally for the smooth delivery of these services. This research was conducted in a company engaged in the field of courier services industry. The sample of this study were 12 consumers of door-to-door shipments issued by courier services. Data analysis was performed using the Saving Matrix method by considering the vehicle's transport capacity and time windows. Time windows used are time intervals that indicate the start time of vehicle usage from the distribution center and the time of return of the vehicle to the distribution center. Calculation of distribution costs by using the saving matrix method obtained cost savings of 3-25%.